Physiological, genetic and genomic analyses of herbicide resistance in grain sorghum (Sorghum bicolor) - Pandian, Balaji Aravindhan (Kansas State University, 2020)
Grain sorghum [Sorghum bicolor (L.) Moench ssp. bicolor] is a versatile crop with multiple uses, including for food, feed, and fuel. Postemergence (POST) grass weed control continues to be a major challenge in grain sorghum, primarily due to a lack of herbicide options registered for POST use. The 4- hydroxyphenylpyruvate dioxygenase (HPPD)- (e.g., mesotrione or tembotrione) and acetolactate synthase (ALS)- inhibitor (e.g., chlorsulfuron) herbicides are used for POST control of a broad-spectrum of weeds including grasses in corn and wheat but not in sorghum, due to crop injury. The development of herbicide-resistant sorghum technology to facilitate broad-spectrum POST weed control can be an economical and viable solution. Previously we have identified four sorghum genotypes, two each resistant to mesotrione (G-1 and G-10), tembotrione (G-200 and G-350) and, one susceptible genotype (S-1) from the sorghum association panel. Further, we found that the genotype S-1 is highly resistant to chlorsulfuron. The objectives of this dissertation were to 1) investigate the inheritance, mechanism, and identify genetic loci conferring resistance to mesotrione and tembotrione, 2) characterize, and investigate the inheritance and mechanism of resistance to chlorsulfuron in grain sorghum. To understand the inheritance of the mesotrione and tembotrione resistance, F₁ and F₂ progeny were generated by performing crosses using S-1 and G-1, G-10, G-200, or G-350. The F₁ and F₂ progeny were evaluated for their response to various doses of mesotrione and tembotrione treatment. Likewise, chlorsulfuron dose-response experiments were conducted using S-1 along with BTx623, a susceptible check and also F₁ and F₂ progeny were generated by crossing S-1 and BTx623. The results of genetic analyses of the F₁ and F₂ progeny demonstrated that the mesotrione resistance in G-1 and G-10 is a single dominant trait, and while the tembotrione resistance in G-200 and G-350 is a partially dominant polygenic trait. Further, sequencing of HPPD gene, the molecular target of mesotrione and tembotrione in the resistant genotypes, revealed no mutations known to bestow resistance. Additionally, the role of cytochrome P450 (CYP) in metabolizing mesotrione and tembotrione, using CYP-inhibitors, malathion and piperonyl butoxide (PBO) was also assessed. The results indicated a significant reduction in biomass accumulation in sorghum plants pre-treated with malathion or PBO, suggesting the involvement of CYPs in the metabolism of mesotrione and tembotrione. Bulk segregation analysis combined with RNA-Seq (BSR-seq) was used to identify the genomic region associated with mesotrione resistance; however, the sequence analyses was unable to map the resistance gene within a smaller interval. Genotype-by-sequencing (GBS) based quantitative trait loci (QTL) mapping revealed three QTLs associated with tembotrione resistance in G-200. The results of the chlorsulfuron dose-response assay indicated that S-1 and F₁ progeny were ~20-fold, more resistant to chlorsulfuron relative to BTx623. Segregation of F₂ progeny into 3:1 (resistance: susceptibility), suggested that chlorsulfuron resistance in S-1 is a single dominant trait. Sequence analysis of the ALS gene, the molecular target of chlorsulfuron from S-1 revealed no mutations that confer resistance to chlorsulfuron; however, a significant reduction in biomass accumulation was found in plants pre-treated with malathion, indicating that the metabolism of chlorsulfuron contributes to resistance in S-1. Overall, the results of this dissertation provide opportunities to develop herbicide-resistant sorghum hybrids via introgression, which can help effective, POST weed management.
Keywords: Sorghum; Herbicide resistance; Mesotrione, tembotrione and chlorsulfuron; Inheritance; Genomic analyses